Haunted - Patterson, James, 1947-; Born, James O. (Patterson, James, 1947- Detective Michael Bennett thriller., 2017)
"Detective Michael Bennett is ready for a vacation after a series of crises push him, and his family, to the brink. He settles on an idyllic, small town in the beautiful Maine woods, a recommendation from a former colleague. But just when Bennett thinks he can relax, he gets pulled into a case that has shocked the tight-knit community. Kids are disappearing left and right with no explanation -- until several bodies turn up in the woods. As Bennett investigates, he discovers that the seemingly perfect town is reeling from a deadly addiction, and the violence is about to reach a fever pitch. Far from the city streets he knows so well, Bennett faces off against a horrific evil next door that threatens a town, the law, and the family that Bennett loves above all else." -- From Amazon.com.